Mr. Ganjar Roso's Traditional Therapy Based on Cultural and Religious Values from a Cross-Cultural Counseling Perspective - Talitha Laksmi Adibah (International Journal of Counseling and Psychotherapy, 2025)
Background: In a multicultural society like Indonesia, traditional medicine based on cultural and religious values plays a significant role as an alternative and complement to modern medical treatment. Objective: This study aims to describe the traditional therapy by Mr. Ganjar Roso in Banyumas, Central Java, from the perspective of cross-cultural counseling. Method: The research employs a qualitative descriptive approach, using data collection techniques such as direct interviews and documentation from the YouTube channel "Ganjars Ngaji Roso." This method allows for an in-depth exploration of the therapeutic practices and their underlying cultural and spiritual values. Result: The findings reveal that Mr. Ganjar's therapy extends beyond physical healing to encompass psychological, emotional, and spiritual aspects. His healing methods include sirasa (spiritual sensitivity), ilmu sabdo (prayers/mantras), and kasunyatan (spiritual silence), which are combined with Islamic practices such as dzikir, shalawat, and the recitation of Al-Fatihah. These practices reflect a holistic approach to counseling that integrates both spiritual and cultural dimensions. Conclusion: Mr. Ganjar's therapy can be viewed as a form of counseling that is holistic, contextual, and deeply aligned with the local cultural and religious values. This approach emphasises the importance of integrating local wisdom and spirituality in the healing process, making it a relevant model for cross-cultural counseling. Contribution: This research contributes valuable insights into how traditional healing practices based on cultural and religious values can serve as an effective alternative in cross-cultural counseling contexts.